Connecting defects and amorphization in UiO-66 and MIL-140 metal–organic frameworks: a combined experimental and computational study. Issue 3 (22nd December 2015) - Bennett, Thomas D.; Todorova, Tanya K.; Baxter, Emma F.; Reid, David G.; Gervais, Christel; Bueken, Bart; Van de Voorde, B.; De Vos, Dirk; Keen, David A.; Mellot-Draznieks, Caroline
Abstract : Ball-milling amorphization of UiO-66, MIL-140B and MIL-140C was observed to proceed by metal–ligand bond breaking, and linked to the generation of successive defects. Abstract : The mechanism and products of the structural collapse of the metal–organic frameworks (MOFs)UiO-66, MIL-140B andMIL-140C upon ball-milling are investigated through solid state 13 C NMR and pair distribution function (PDF) studies, finding amorphization to proceed by the breaking of a fraction of metal–ligand bonding in each case. The amorphous products contain inorganic–organic bonding motifs reminiscent of the crystalline phases. Whilst the inorganic Zr6 O4 (OH)4 clusters ofUiO-66 remain intact upon structural collapse, the ZrO backbone of theMIL-140 frameworks undergoes substantial distortion. Density functional theory calculations have been performed to investigate defective models ofMIL-140B and show, through comparison of calculated and experimental 13 C NMR spectra, that amorphization and defects in the materials are linked.